Risk analysis of heavy metal concentration in surface waters across the rural-urban interface of the Wen-Rui Tang River, China. (June 2018) - Qu, Liyin; Huang, Hong; Xia, Fang; Liu, Yuanyuan; Dahlgren, Randy A.; Zhang, Minghua; Mei, Kun
Abstract: Heavy metal pollution is a major concern in China because of its serious effects on human health. To assess potential human health and ecological risks of heavy metal pollution, concentration data for seven heavy metals (As, Pb, Cd, Cr, Hg, Cu, Zn) from 14 sites spanning the rural-urban interface of the Wen-Rui Tang River watershed in southeast China were collected from 2000 to 2010. The heavy metal pollution index (HPI), hazard index (HI) and carcinogenic risk (CR) metrics were used to assess potential heavy metal risks. Further, we evaluated the uncertainty associated with the risk assessment indices using Monte Carlo analysis. Results indicated that all HPI values were lower than the critical level of 100 suggesting that heavy metal levels posed acceptable ecological risks; however, one site having an industrial point-source input reached levels of 80–97 on several occasions. Heavy metal concentrations fluctuated over time, and the decrease after 2007 is due to increased wastewater collection. The HI suggested low non-carcinogenic risk throughout the study period (HI < 1); however, nine sites showed CR values above the acceptable level of 10 −4 for potential cancer risk from arsenic in the early 2000s. Uncertainty analysis revealed an exposure risk for As at all sites because some CR values exceeded the 10 −4 level of concern; levels of Cd near an old industrial area also exceeded the Cd exposure standard (2.6% of CR values > 10 −4 ). While most metrics for human health risk did not exceed critical values for heavy metals, there is still a potential human health risk from chronic exposure to low heavy metal concentrations due to long-term exposure and potential metal interactions. Results of this study inform water pollution remediation and management efforts designed to protect public health in polluted urban area waterways common in rapidly developing regions. Graphical abstract: Image 1 Highlights: Six heavy metal contaminations in surface water of Wen-Rui Tang River were evaluated. The heavy metal pollution index fluctuated throughout the study period. Spatial hotspots of heavy metal were around industrial point-sources. Arsenic was the major pollutant for human-health concern especially in the northern part of the urban area. Uncertainty analysis showed a probably potential carcinogenic risk of cadmium. Abstract : This study provided a quantitative assessment and uncertainty measures that identified specific hotspots for heavy metal contamination and human health risks.